Etyka niejawnej obserwacji uczestniczącej jako metody badawczej stosowanej w naukach społecznych = The ethics of covert participant observation as a research method applied in social studies - Nieporowski, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Covert participant observation is an example of ethically controversial quality method applied in social studies. This article presents the main dilemmas faced by researchers analysing difficult environments in order to gather valuable data in the most harmless for the subjects of their research way. The knowledge about the possible strategies is provided by three quoted examples of field research carried out in isolated environments.
Keywords: niejawna obserwacja uczestnicząca; badania jakościowe; etyka badań naukowych